Anthropometric characteristics and physical performance of colombian elite male wrestlers - Ramirez-Velez, R.; Argothyd, R.; Meneses-Echavez, J. F.; Sanchez-Puccini, M. B.; Lopez-Alban, C. A.; Cohen, D. D. (Asian Journal of Sports Medicine, 2014)
Background: Wrestling was an important part of the ancient Olympic Games and is still one of the most popular events of the modern Olympic Games. Studies indicate that general physiologic profile of successful wrestlers is high anaerobic power and capacity, muscular strength, above average aerobic power, exceptional flexibility, fat free mass, and a mesomorphic somatotype.